MODERNISASI PENDIDIKAN PESANTREN - Husnul Khotimah (Raudhah - Proud To Be Professional, 2022)
As traditional Islamic educational institutions, pesantren are often identified as conservative, static and lagging educational institutions. This kind of stereotype cannot be fully justified, because in fact, Islamic boarding schools continue to transform both institutionally, system, curriculum, etc. related to the development of the pesantren curriculum, not many researchers and academics have taken concern in this field of study. This research is a literature review based on several previous studies. The results of this study show several conclusions. First, as a traditional Islamic education institution in Indonesia, pesantren have shown success in maintaining their existence amidst globalization. Second, the pesantren curriculum has several aspects of excellence, including; aspects of identity, continuity, independence and flexibility. However, the pesantren curriculum also has drawbacks, namely centric Kiai and Alineasi (alienation). Third, the components that must be owned by the pesantren education curriculum consist of; objectives, knowledge content and learning experiences, strategy and evaluation.